KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGELOLA TENAGA KEPENDIDIKAN - Waliman Waliman; Aliman Aliman; Puspa Djuwita (Manajer Pendididikan, 2017)
The problem of the research is how headmaster leadership to manage education employers in Senior High School Number 1 Putri Hijau, North Bengkulu Region. The purpose of  this research can describe to the headmaster to make planning, organizing, motivating, controlling, support and the hampers of headmaster leadership to manage education employers. This reasearch use destiptive qualitative method with the subject is headmaster, deputy headmaster and administration. Do controlling data with observation technic, interview and documentation. The result of research from recruit of data from several data subject and the conclution is that the headmaster leadership of Senior High School Number 1 Putri Hijau, North Bengkulu Region is democration leadership style